Are the same tapes really the same? Ultrasound study of laser-cut and mechanically cut TVT-O post-operative behavior. (September 2018) - Rusavy, Zdenek; Masata, Jaromir; Svabik, Kamil; Hubka, Petr; Zvara, Karel; Martan, Alois
Abstract Introduction and hypothesis TVT-O production has been modified to laser cutting from mechanical cutting. We compared the behavior of laser and mechanically cut tension-free vaginal tape-obturator (TVT-O) using ultrasound at various time points after surgery. Methods This is a retrospective analysis of clinical and ultrasound data from two previously reported randomized controlled trials with TVT-O. Behavior of mechanically cut TVT-O implanted in January 2007 to November 2009 and laser-cut TVT-O implanted in May 2010 to May 2012 was assessed by ultrasound at day 1, the 2nd week, the 3rd month, and the 1st and 2nd years post-operatively. Bladder neck and tape margins positions were described by coordinates in the orthogonal system calculated from polar coordinates. Tape mobility was measured as a change in the upper and lower tape margin position from rest to maximal Valsalva. Comparison of 2-year subjective and objective surgery outcomes was also performed. Results In total, 68 mechanically cut and 50 laser-cut TVT-Os were implanted. Follow-up data were available from 49 and 45 women respectively. No differences in any baseline characteristics or bladder neck mobility were observed. Significantly lower tape mobility was observed on day 1 and week 2 after mechanically cut TVT-O, although subsequent mobility was comparable to laser-cut TVT-O. The subjective and objective surgery outcomes were comparable. Conclusions Although without clinical significance, early postoperative behavior of the mechanically cut and laser-cut TVT-O tapes differs. The less stiff, mechanically-cut TVT-O loosens within 2 weeks of implantation, whereas the stiffer, laser-cut TVT-O keeps its tension.